The Influence of EPS and POFA as Replacement Material in the Production of Non-Load Bearing Brick - Jamiran, Siti Nur Syafiqah; Mohd yassin, Nurain Izzati (Recent Trends in Civil Engineering and Built Environment, 2024)
The purpose of this study was to investigate the influence of expanded polystyrene (EPS) and palm oil fuel ash (POFA) as replacement materials in the production of lightweight concrete brick. In this study, sand was replaced by EPS by 30%, 40%, and 50% of its volume in the concrete brick mixture. POFA, on the other hand, was replaced 10% of the cement volume. The replacement materials were used to prepare a concrete brick with dimensions of 215mm x 103mm x 65mm. Concrete bricks constituting EPS and POFA were evaluated in terms of density, compressive strength, and water absorption. Before the test, these samples were undergoing air curing process for 7 and 28 days, respectively. The performance of concrete bricks incorporating EPS and POFA as replacement materials were compared to the performance of ordinary concrete bricks. The desirable percentage of EPS and POFA was determined with the aid of the findings. The consumption of EPS and POFA in the production of non-load bearing brick were effective to lessen production costs while also designing a more sustainable environment for our future generations.